2021
DOI: 10.1111/evj.13444
|View full text |Cite
|
Sign up to set email alerts
|

Active equine parvovirus‐hepatitis infection is most frequently detected in Austrian horses of advanced age

Abstract: Background Equine parvovirus‐hepatitis (EqPV‐H) research is in its infancy. Information regarding prevalence, geographical distribution, genetic diversity, pathogenesis and risk factors enhances understanding of this potentially fatal infection. Objectives Determining the prevalence of EqPV‐H in Austrian equids. Investigating factors increasing probability of infection, liver‐associated biochemistry parameters, concurrent equine hepacivirus (EqHV) infection and phylogenetic analysis of Austrian EqPV‐H variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
43
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 25 publications
15
43
4
Order By: Relevance
“…Increasing age as a risk factor for EqPV-H infection was further supported by the findings of a surveillance study in Austrian horses. In this study the highest infection prevalence was found in 16to 31-year-old horses [33]. A recent study by Tomlinson et al reported EqPV-H in foals for the first time, with 79% (19/24) of foals that were EqPV-H PCR-negative at birth, becoming PCR-positive within their first year of life [21].…”
Section: Risk Factors: Age Breeding and Seasonsupporting
confidence: 46%
See 1 more Smart Citation
“…Increasing age as a risk factor for EqPV-H infection was further supported by the findings of a surveillance study in Austrian horses. In this study the highest infection prevalence was found in 16to 31-year-old horses [33]. A recent study by Tomlinson et al reported EqPV-H in foals for the first time, with 79% (19/24) of foals that were EqPV-H PCR-negative at birth, becoming PCR-positive within their first year of life [21].…”
Section: Risk Factors: Age Breeding and Seasonsupporting
confidence: 46%
“…Recently, all 12 publicly available complete coding sequences (CDS) of the species Ungulate copiparvovirus 6 —obtained in China and the United States—were compared with the CDS of four Austrian variants and found to be closely related 33 . The genetic diversity of the NS and VP genes appears to be low among different EqPV‐H variants in the United States, China, Canada, New Zealand, Italy, and Germany, indicating high conservation and low genetic variability of variants circulating globally 16,25,32,35,37 .…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…In Europe, viral loads of 1.26 × 10 4 to 2.04 × 10 9 genome equivalents (GE)/million cells were detected in liver tissue of four horses suffering from Theiler’s disease [ 13 ]. In healthy horses in the USA, China, Germany and Austria a DNA prevalence for EqPV-H has been reported between 7% and 17% [ 8 , 14 , 15 , 16 , 17 , 18 ] compared to a markedly higher DNA prevalence between 54% and 79% in farms in the USA and Canada with recently documented cases of Theiler’s disease [ 10 , 12 , 19 ]. Current research is focused on disease outbreaks, possible transmission and seroprevalence in horse populations.…”
Section: Introductionmentioning
confidence: 99%
“…Real time PCR tests performed by Cornell University Animal Health Diagnostic Center reported negative results for the flavivirus equine hepacivirus and positive results for equine parvovirus (EqPV-H) with Ct values of 32.36. EqPV-H, a frequent equine infection [34,35], has been associated with and shown to induce hepatitis following inoculation although many EqPV-H infections are also asymptomatic [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Here a horse with a mild case of hepatitis was infected with a circovirus but also viremic at low levels (real time PCR Cut off 34) with the hepatotropic EqPV-H. Although many asymptomatic EqPV-H infections have been reported [34,35] EqPV-H detection in this horse does provides a conceivable explanation for its hepatitis [36,38]. Whether EqCV1 played a leading, supporting, or no role in this case of hepatitis or has the potential to cause other equine diseases will require further studies.…”
Section: Discussionmentioning
confidence: 99%